Evaluating the Effectiveness of Criminal Law Policies in Reducing Narcotics Abuse in Medan City: A Mixed-Methods Study - Simangunsong, Humala; Freitas, Jose Lemos; Shrestha, Polanski Snyder (Institute for Law and Economics Studies, 2023)
Narcotics abuse is a pressing issue with profound implications for public health, social well-being, and community resilience in Medan City. This research investigates the effectiveness of existing criminal law policies in mitigating narcotics abuse, employing a mixed-methods approach that integrates quantitative and qualitative analyses. The quantitative analysis, drawing from law enforcement records and health institutions, reveals a cyclic pattern in drug-related incidents, demonstrating short-term declines following intensified law enforcement actions, which are subsequently followed by resurgences in narcotics-related activities. The adaptability of drug trade networks poses a formidable challenge, emphasizing the need for flexible and evolving law enforcement strategies. Qualitative insights, gathered through interviews with various stakeholders, underscore the significance of socioeconomic factors in perpetuating drug abuse. The limitations in current rehabilitation and support programs, alongside the necessity for improved access and outreach, are apparent. Stakeholders advocate for a balanced and comprehensive approach that integrates preventive education, mental health support, and robust rehabilitation programs. The research carries implications for policy development, public health strategies, and community engagement. Effective policy measures are identified as the cornerstone of efforts to address narcotics abuse, while the need for community resilience and public health support is underlined. Furthermore, the implications extend beyond Medan City, offering valuable lessons for similar regions grappling with drug-related challenges. This research serves as a guidepost for refining existing policies, fostering collaboration, and developing more robust strategies to promote a healthier and more resilient Medan City. The battle against narcotics abuse is an ongoing endeavor, and the insights gained from this study are instrumental in shaping a brighter and more drug-resistant future for the city and its residents.